2016
DOI: 10.1177/1557988316639050
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Periodontal Disease and Erectile Dysfunction: A Systematic Review

Abstract: A limited number of studies have reported an association between erectile dysfunction (ED) and chronic periodontitis (CP). The aim of the present study is to assess the association between CP and ED through a systematic review of published literature. To address the focused question, "Is there a relationship between ED and CP?" indexed databases were searched till December 2015 using various key words "erectile dysfunction," "periodontal disease," "periodontitis," "dental infection," and "impotence." Letters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…It should also be taken into account that in the current study, ED was only determined through self-report. It is recommendable to establish ED diagnosis after a complete physical and psychological evaluation to determine vasculogenic or psychogenic factors ( Cavallini, 2016 ; Kellesarian et al, 2016 ). This study was motivated after the complaints observed in the clinical practice about ED.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be taken into account that in the current study, ED was only determined through self-report. It is recommendable to establish ED diagnosis after a complete physical and psychological evaluation to determine vasculogenic or psychogenic factors ( Cavallini, 2016 ; Kellesarian et al, 2016 ). This study was motivated after the complaints observed in the clinical practice about ED.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation may be an intermediary explanatory variable in the association between the increase in the retinal vessel diameters and periodontitis (Boillot et al., ). Further, associations between microvascular abnormalities and periodontitis were also reported for other final microcirculation areas, for example for the erectile dysfunction (Kellesarian et al., ). Periodontitis has been associated with several conditions, including vascular dysfunction, and may impact microvascular endothelium function.…”
Section: Discussionmentioning
confidence: 88%
“…A recent systematic review found a significant positive relationship between PD and erectile dysfunction 26 . Both conditions share chronic inflammation and systemic endothelial dysfunction, which are also key mechanisms of carcinogenesis 27 .…”
Section: Discussionmentioning
confidence: 99%